The effects of corporate governance mechanisms on earnings management: Empirical evidence from Moroccan listed firms - Yousra El Mokrani; Youssef Alami (Goodwood Publishing, 2021)
Purpose: The purpose of the study is to systematically review and examine the effectiveness of corporate governance mechanisms in restraining earnings management among the listed firms of the Casablanca Stock Exchange. Research methodology: In this study, we used the modified Jones model to calculate discretionary accruals. Our sample comprises 27 firms covering the period from 2016 to 2018, analyzed by the EGLS estimator. Results: Our empirical results show that gender diversity, board size, and audit committee independence reduce the managers' discretion. Simultaneously, we found a significantly positive association between earning management and different corporate governance characteristics such as CEO duality, institutional investor ownership, and family ownership. We do not find any evidence that audit committee size, ownership concentration, and managerial ownership significantly influence discretionary accruals. Limitations: This study's main limitation is that we did not address the direction of discretionary accruals, which does not allow us to detect the motivational aspects behind earnings management. Contribution: The results of this study will help Moroccan authorities in their formulation of an appropriate regulatory framework because very few studies have been conducted in this area in the case of the Moroccan listed companies, especially with a large set of governance variables as our empirical model.